Phenotypic switching of vascular smooth muscle cells in the 'normal region' of aorta from atherosclerosis patients is regulated by miR‐145. Issue 6 (15th March 2016) - Zhang, Yu‐nan; Xie, Bao‐dong; Sun, Lu; Chen, Wei; Jiang, Shu‐Lin; Liu, Wei; Bian, Fei; Tian, Hai; Li, Ren‐Ke
Abstract: Switching of vascular smooth muscle cells (VSMCs) from a contractile phenotype to an adverse proliferative phenotype is a hallmark of atherosclerosis or vascular restenosis. However, the genetic modulators responsible for this switch have not been fully elucidated in humans nor have they been correlated with clinical abnormalities. This study investigated genetic mechanisms involved in phenotypic switching of VSMCs at non‐defect areas of the aorta in patients with atherosclerosis. Aortic wall samples were obtained from patients with ( N = 53) and without ( N = 27) atherosclerosis undergoing cardiovascular surgery. Vascular smooth muscle cell cultures were generated, and expression of microRNA‐145 ( miR‐145 ), its target gene Kruppel‐Like Factor 5 (KLF5) and Myocardin (MYOCD, a smooth muscle‐specific transcriptional coactivator) were analysed using RT‐qPCR, along with expression of relevant proteins. Vascular smooth muscle cells were transduced with miR‐145 inhibitor and mimic to determine the effect of miR‐145 expression on VSMC proliferation. miR‐145 expression decreased while KLF5 expression increased in atherosclerotic aortas. Atherosclerotic samples and VSMCs had decreased expression of contractile markers calponin and alpha smooth muscle actin (α‐SMA) and MYOCD. miR‐145 inhibitor‐transduced VSMCs from non‐atherosclerotic patients showed decreased expression of calponin and α‐SMA and increased proliferation compared with non‐transduced controls, and these levels were close to those of atherosclerotic patients. miR‐145 mimic‐transduced VSMCs from atherosclerotic patients showed increased expression of calponin and α‐SMA and decreased proliferation compared with non‐transduced controls, and these levels were close to those found in non‐atherosclerotic patients. These data demonstrate that miR‐145 modulates the phenotypic switch of VSMCs from a contractile to a proliferative state via KLF5 and MYOCD in atherosclerosis.